ReSySTER: A hybrid recommender system for Scrum team roles based on fuzzy and rough sets - Colomo-Palacios, Ricardo; González-Carrasco, Israel; López-Cuadrado, José Luis; García-Crespo, Ángel (Zielona Góra: Uniwersytet Zielonogórski)
Agile development is a crucial issue within software engineering because one of the goals of any project leader is to increase the speed and flexibility in the development of new commercial products.
Keywords: fuzzy sets; rough sets; Scrum; work package; recommender system